Improvement of Subgrade Soils by Using Marble Dust-(Libya, Case Study) (The International Journal of Engineering & Information Technology (IJEIT), 2020)
the practice of using waste materials to modify theproperties of poor soils has become increasingly important ingeotechnical engineering. In recent years, much research hasbeen devoted to the effect of this waste material on soilproperties. This study aims to address the influence of marbledust powder on the performance of subgrade. Thus, soilsmixed with different percentages of marble dust were tested.The CBR test and modified proctor have been used toevaluate the performance of the soils mixed with marble dust.The statistical analysis illustrated that marble dustsignificantly enhanced the properties of the soils. The studyconcludes that an addition of 10% of marble dust to untreated(control) soils yields the most satisfactory results among otherpercentages of marble dust. The study recommends the use ofmarble dust in geotechnical construction.